The Main Character Analysis in “The Diamond Necklace” by Guy De Maupassant - Ika Handayani; Eri Rahmawati (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2023)
The present study aims to describe the inferiority feeling and striving for superiority aspects of the main character,